The role of glucose in the pathology of EHEC O157: H7 - Marques Da Silva, Wanderson; Taibo, Catalina Beatriz; Sabio Y Garcia, Julia Veronica; Larzabal, Mariano; Cataldi, Angel Adrian (Cambridge University Press, 2021)
The pathogen enterohemorrhagic Escherichia coli (EHEC) O157: H7 is responsible for hemorrhagic colitis and hemolytic uremic syndrome in humans [1]. During the colonization process in the gastrointestinal tract, EHEC needs to adapt to changes in nutrient availability [2]. The objective of this study was to evaluate the influence of glucose on physiology and processes involved in the pathogenesis of EHEC O157: H7 in order to improve our understanding of the mechanisms controlling EHEC growth and survival in the bovine gut. In this study we first analyzed the growth rate of EHEC O157: H7 Rafaela II clade 8, a strain isolated from a bovine in Argentina, grown in the medium DMEM supplemented with either 4.5% glucose (Highglucose - DHG) or 1% glucose (Low-glucose - DLG). In addition, we assessed the bacterial adhesion capacity and actin pedestal formation induced by EHEC [3] by performing infection assays. For this purpose, Caco-2 epithelial cells were exposed for 5 h with Rafaela II grown with the different concentrations of glucose. Subsequently, the samples were fixed (paraformaldehyde 4%) and permeabilized (triton); actin and nucleic acids (DNA) were stained with rhodamine-phalloidin and TOPRO-3, respectively. Bacterial adhesion capacity and pedestal formation of cells were evaluated using a Leica TCS SP5 laser scanning confocal microscope (MC). Each Image was acquired by monitoring a single focal plane over time (xyt scanning mode) using a 40X/1.25 oil objective lens and 543nm HeNe and 633 nm HeNe lasers. The frequency and resolution for acquiring images were set at 200 Hz and 1,024 x 1,024 pixels, while maintaining the same settings for laser powers, gain, and offset.